The Acquisition Of Negation By Malay ESL Learners - Wan Chik, Suliana (2009)

(untitled)
It has been observed that Malay learners of English as a Second Language (ESL) have difficulty with sentential negation in English. It is postulated that the difficulty could be due to properties related to English negation that are not found in Malay. These are the not-placement rule and do-support rule in English. In English, various types of auxiliary verbs (modal, aspect and passive auxiliaries) can co-exist simultaneously in a sentence as in The book might have been being stolen by Tom. In a negative construction, the not-placement rule states that the negative particle not should be placed after the first auxiliary verb as in The book might not have been being stolen by Tom. This condition, however, does not apply in Malay as the language does not permit more than one auxiliary in a sentence. Additionally, unlike English, a do-support language, Malay does not require an auxiliary to be present in sentential negation with thematic verbs. Inability to conform to these rules may result in the production of ungrammatical English sentences among the Malay ESL learners. This study investigates the Interlanguage of English negation among Malay ESL learners. Specifically, the study reports the extent to which learners are able to acquire English sentential negation with the copula be verb, auxiliary verb and with thematic verbs (which needs do-support) and see if transfer from the L1 is involved in the process. This cross-sectional study focused on 90 Malay learners. They were categorized into three levels of proficiency based on their age and performance on a standardized proficiency test (the Oxford Placement Test). Instrumentation for the study includes a grammaticality judgment task and an elicited translation task. The results indicate a gradual staged development from the elementary group to the advanced group, both in terms of age and proficiency level. It is also noted that learners seem to find sentential negation with the copula be more difficult than auxiliary verbs and thematic verbs. Two implications can be drawn from the findings. The first are the expectations ESL instructors bring to the classroom relative to the performance of our students. The second is how the presence of developmental sequences in learner language might influence what these instructors teach.